2014
DOI: 10.1073/pnas.1404545111
|View full text |Cite
|
Sign up to set email alerts
|

The docking protein FRS2α is a critical regulator of VEGF receptors signaling

Abstract: Significance Regulation of vascular endothelial growth factor (VEGF) signaling plays a central role in a range of biological processes from embryonic and perinatal vascular development to maintenance of the mature adult vasculature to regulation of various organs function. We report that the intracellular docking protein FRS2α, not hitherto known to be involved in VEGF signaling, plays a critical role in regulation of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Therefore, TDF and other NRTI treatments may restrain VEGF‐C‐induced neovessel formation by enhancing the binding of VEGF‐C to VEGFR3 in endothelial cells. On the other hand, the suppression by NRTIs of FGF‐induced angiogenesis may be partly due to the blockage of the FGF signalling‐maintained VEGFR2 expression (Murakami et al, ) and an effect on the docking protein FRS2α that would adapt the crosstalk between the two RTK pathways (Chen et al, ). Since the dose of NRTIs in the present study was similar to the serum concentration found in clinical treatments, these experimental phenotypes may reflect the development of endothelial dysfunction and impairments in angiogenesis/lymphangiogenesis in patients receiving ART therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TDF and other NRTI treatments may restrain VEGF‐C‐induced neovessel formation by enhancing the binding of VEGF‐C to VEGFR3 in endothelial cells. On the other hand, the suppression by NRTIs of FGF‐induced angiogenesis may be partly due to the blockage of the FGF signalling‐maintained VEGFR2 expression (Murakami et al, ) and an effect on the docking protein FRS2α that would adapt the crosstalk between the two RTK pathways (Chen et al, ). Since the dose of NRTIs in the present study was similar to the serum concentration found in clinical treatments, these experimental phenotypes may reflect the development of endothelial dysfunction and impairments in angiogenesis/lymphangiogenesis in patients receiving ART therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is because Frs2 binds a number of RTKs in addition to Fgfrs that include Trks, Ret, Alk, and Vegfrs (Rabin et al 1993;Ong et al 1996Ong et al , 2000Dhalluin et al 2000;Kurokawa et al 2001;Melillo et al 2001;Degoutin et al 2007;Chen et al 2014b). Loss of Frs2 therefore alters signaling downstream from multiple RTKs, making the phenotypes of Frs2…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…24 Activation of these receptor tyrosine kinases allows FRS2 proteins to become phosphorylated at tyrosine residues and then bring about a cascade of events including activation of the Ras/ERK, PI3kinase and MAPK pathway. 25 This may among others affect neurite outgrow. 26 | 1291 affect angiogenesis as well as actin reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…VONK ET AL.| 1291affect angiogenesis as well as actin reorganization 25. In bold; significantly replicated SNPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation